2019
DOI: 10.1002/adsc.201900391
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of β‐Isoxazole Carbonyl Derivatives and their Analogues via Palladium‐Catalyzed Sequential C(sp2)−O/C(sp2)−C(sp3) Bond Formations

Abstract: An efficient Pd(II)‐catalyzed one‐pot tandem cyclization/alkylation reaction of internal alkynes has been reported. In this reaction, a wide range of structurally diverse β/;‐isoxazole aldehydes/ketones could be obtained in good to excellent yields from various alkynyl oxime ethers and allylic or homoallylic alcohols. The gram‐scale experiment and various transformations of the newly obtained products demonstrated that this method should be a general and useful synthetic tool.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…On the basis of the obtained experimental results and previous relevant reports, [19a,20b,21b,23] a tentative reaction mechanism involving chain walking process is proposed (Scheme 5). In the presence of excess bromine ions, oxypalladation of alkynone O ‐methyloximes 1 gives vinyl palladium species I , [19a] followed by migration of alkene 2 to afford alkyl‐palladium species II [23b] . Subsequently, intermediate II undergoes consecutive β ‐hydride elimination and coordination of HPdX species generates the intermediate III [3b,24] .…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the obtained experimental results and previous relevant reports, [19a,20b,21b,23] a tentative reaction mechanism involving chain walking process is proposed (Scheme 5). In the presence of excess bromine ions, oxypalladation of alkynone O ‐methyloximes 1 gives vinyl palladium species I , [19a] followed by migration of alkene 2 to afford alkyl‐palladium species II [23b] . Subsequently, intermediate II undergoes consecutive β ‐hydride elimination and coordination of HPdX species generates the intermediate III [3b,24] .…”
Section: Resultsmentioning
confidence: 99%
“…In (Scheme 40) shows a one‐pot tandem Pd(II)‐catalyzed cyclization/alkylation process of internal alkynes [61]. Several alkynyl oxime ethers 1 and allylic or homoallylic alcohols 2 were used in this reaction to produce a wide range of structurally varied ß\ɷ‐ isoxazole aldehydes/ketones 3 in good to outstanding yields.…”
Section: Synthetic Methods Of Isoxazole and Their Derivativesmentioning
confidence: 99%
“…The 3-amino-5-(methyl/t-butyl)isoxazoles 1 were utilized as key starting materials for the synthesis of the new compounds. The isoxazole-thiazolone derivatives 2 were synthesized by heating compound 1 with S C H E M E 4 0 Synthesis of diverse ß/ ɷ-isoxazole aldehydes/ketones derivatives [61] S C H E M E 4 1 Synthesis of isoxazole under TEMPO-catalyzed aerobic conditions [62] S C H E M E 4 2 Synthesis of 3, 5-(bis)isoxazole via intramolecular N-O bond formation [63] S C H E M E 4 3 An intramolecular Wittig approach for the synthesis of isoxazoles [64] S C H E M E 4 4 An intramolecular cyclization approach for the synthesis of isoxazoles [65] ammonium thiocyanate in refluxing ethanol. The reaction of 2 with aromatic aldehydes in presence of an ethanolic solution of sodium hydroxide gave the corresponding 5-arylidenethiazolone-isoxazole derivatives 3 as depicted in Scheme 49.…”
Section: Other Synthetic Routesmentioning
confidence: 99%
“…For instance, Chen and co-workers revealed a cascade cyclization/alkenylation with activated alkenes (Scheme b) . Alkynes were also coupled in tandem in a similar manner (Scheme c) by Jiang et al The same group later reported an interesting redox coupling of allyl alcohols to construct 4-alkylated isoxazoles (Scheme d) …”
Section: Introductionmentioning
confidence: 96%
“…10 Alkynes were also coupled in tandem in a similar manner (Scheme 1c) 11 by Jiang et al The same group later reported an interesting redox coupling of allyl alcohols to construct 4alkylated isoxazoles (Scheme 1d). 12 Surprisingly, the incipient alkenyl-palladium intermediate could not be molded for successive activation of C−H bonds in spite of its availability at a reachable distance on both sides (Scheme 1e, Ar 1 & Ar 2 ). With our persistent interest in the combined alkyne/C−H activation, 13 we herein reveal the tactic of annulating maleimides in succession to isoxazole formation by successfully transporting the Pd center from C-4 to the C− H bond of arene.…”
Section: ■ Introductionmentioning
confidence: 99%